P83 Evans syndrome with abdominal discomfort: a case report. (June 2019) - Zia, Muhammad; Ahmad, Riaz; Liqa UR, REHMAN; Shori, Naeem; Wallis, Maybelle; Jawad, Muhammad; Azam, Muhammad
Abstract : Background: A 15 year old boy, a known case of Evans Syndrome with a feeling of discomfort in his abdomen. Case report: 15 year old boy was presented to emergency department with a feeling of discomfort in his abdomen from last 3 weeks.He also felt a lump on right side of his abdomen. There was no associated history of fever, weight loss, poor appetite, constipation, vomiting or night sweats.On examination boy had a firm rounded mass of about 10x15 cm extending from umblicus to right hypochondrium with irregular surface and no tenderness.Serum LDH was raised 2200IU/ml at admission.Abdominal Ultrasound revealed large lobulated heterogeneous hyper vascular mass in right iliac fossa.CT was requested that demonstrated the presence of large lobulated heterogeneous mass involving caecum, ascending colon and associated hepatic flexure confirming the diagnosis of proximal large bowel lymphoma with accompanying extensive intra peritoneal and retro peritoneal lymph nodes.It also showed lobulated lymph node mass of 8.5x6.5 cm in retro vesicular recess. Mediastinal and axillary lymph nodes were noted on CT thorax. Histopathological examination confirmed the diagnosis of high grade B-cell lymphoma.Regarding past history he was diagnosed as Evans syndrome at the age of 3 years, resistant to treatment and splenectomy was done at the age of 7 years.No significant family history of note.He was treated with 4 courses of chemotherapeutic agents and disease was cured. Discussion: Evans syndrome is a rare autoimmune disorder with no known genetic basis.It usually presents with coombs positive hemolytic anmeia with thrombocytopenia.Because of its autoimmune nature it exhibit signs of lymphoid hyperplasia with increased risk of lymphoreticular malignancies.Prognosis for B cell lymphoma is usually good as it was in our case.